Odpowiedź:
[tex]Zad.1\\\\d)\\\\\begin{cases}2x-3y=0,7\\x+4y=5,3\end{cases}\\\\\\\begin{cases}2x-3y=0,7\\x=5,3-4y\end{cases}\\\\\\2(5,3-4y)-3y=0,7\\\\10,6-8y-3y=0,7\\\\-11y=0,7-10,6\\\\-11y=-9,9\ \ /:(-11)\\\\y=0,9\\\\\\x=5,3-4*0,9=5,3-3,6=1,7\\\\\\\begin{cases}x=1,7\\y=0,9\end{cases}[/tex]
[tex]e)\\\\\begin{cases}x-3y=1-x-y\\0,2x+0,1y=-0,1\end{cases}\\\\\\\begin{cases}x-3y+x+y=1\\0,2x+0,1y=-0,1\ \ /:0,1\end{cases}\\\\\\\begin{cases}2x-2y=1\\2x+y=-1\end{cases}\\\\\\\begin{cases}2x-2y=1\\y=-1-2x\end{cases}\\\\\\2x-2(-1-2x)=1\\\\2x+2+4x=1\\\\6x=1-2\\\\6x=-1\ \ /:6\\\\x=-\frac{1}{6}\\\\\\y=-1-\not2^1*(-\frac{1}{\not6_{3}})=-1+\frac{1}{3}=-\frac{2}{3}\\\\\\\begin{cases}x=-\frac{1}{6}\\y=-\frac{2}{3}\end{cases}[/tex]